Tumour forming Pseudoangiomatous stromal hyperplasia: a case report - R., Vasuki; N. B., Thanmaran; Devi, A. K. Kalpana; Moothedath, Rajesh Menon; M., Satheesh Kumar (International Surgery Journal, 2017)
Tumor-forming Pseudoangiomatous stromal hyperplasia (PASH) is a rather uncommon breast lesion and only very few cases of tumor-forming PASH were reported from 1986, since the lesion was originally described. In contrast, focal, non-tumor forming PASH may be an incidental microscopic finding in up to 23% of breast biopsies. PASH is a benign proliferative lesion of the breast stroma that is characterized by slit-like pseudovascular spaces lined by endothelial-like spindle cells. It is indeed rare for a discrete breast mass to have PASH as the main pathological feature on histopathology. The breast mass, typically unilateral, was usually diagnosed clinically as a fibroadenoma.When found in tumour form, PASH most commonly manifests as a single, circumscribed, palpable mass in a premenopausal female. The main differential diagnosis histologically are fibroadenoma, phyllodes tumor and angiosarcoma. However, PASH is a benign condition with very good prognosis. Hence possibility of PASH in nodular or tumour form has to be considered when approaching a case of breast lump whose management is different. We report here a case of PASH in tumour form from our Institute.